Carbon-Based Nanomaterials 3.0 - Díez-Pascual, Ana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Carbon-based nanomaterials are incredible tools with exceptional properties (high mechanical strength, high conductivity, attractive optical properties, chemical versatility, etc.). Among them, graphene and carbon nanotubes are the most frequently used from a practical viewpoint. These carbon nanomaterials can be synthesized by several methods, including top-down and bottom-up approaches. Their characterization via Raman spectroscopy, electron microscopy and atomic force microscopy is essential to correlate their structure with their properties in order to use them for specific applications. They show a brilliant future that is envisaged in the current reprint, which provides selected examples of the most recent advances in the preparation and characterization of carbon nanotube and graphene-based nanomaterials for a variety of applications.